Evolution of Archamoebae: morphological and molecular evidence for pelobionts including Rhizomastix, Entamoeba, Iodamoeba, and Endolimax - Ptáčková, Eliška; Kostygov, Alexei Yu; Chistyakova, Lyudmila V; Falteisek, Lukáš; Frolov, Alexander O; Patterson, David J; Walker, Giselle; Cepicka, Ivan (Protist, 2013)
The archamoebae form a small clade of anaerobic/microaerophilic flagellates or amoebae, comprising the pelobionts (mastigamoebids and pelomyxids) and the entamoebae. It is a member of the eukaryotic supergroup Amoebozoa. We examined 22 strains of 13 species of Mastigamoeba, Pelomyxa and Rhizomastix by light-microscopy and determined their SSU rRNA gene sequences. The SSU rRNA gene sequences of Pelomyxa palustris and Mastigella commutans in GenBank are shown to belong to P. stagnalis and Mastigamoeba punctachora, respectively. Five new species of free-living archamoebae are described: Mastigamoeba abducta, M. errans, M. guttula, M. lenta, and Rhizomastix libera spp. nov. A species of Mastigamoeba possibly living endosymbiotically in Pelomyxa was identified. Rhizomastix libera, the first known free-living member of that genus, is shown to be an archamoeba. R. libera possesses an ultrastructure unique within archamoebae: a rhizostyle formed from a modified microtubular cone and a flagellum with vanes. While many nominal species of pelobionts are extremely hard to distinguish by light microscopy, transient pseudopodial characters are worthy of further investigation as taxonomic markers.
Keywords: molekulární evoluce; Endolimax; geny rRNA; druhová specificita; Phylogeny; Archamoebae; mikroskopie; Sequence Analysis, DNA; Evolution, Molecular; Genes, rRNA; protozoální DNA; DNA, Protozoan; zvířata; Entamoeba; sekvenční analýza DNA; fylogeneze; Species Specificity; Animals; Microscopy